2015
DOI: 10.1128/aem.02601-14
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics-Aided Dissection of the Intracellular and Extracellular Roles of Microcystin in Microcystis aeruginosa PCC 7806

Abstract: e Recent studies have provided evidence for both intracellular and extracellular roles of the potent hepatotoxin microcystin (MC) in the bloom-forming cyanobacterium Microcystis. Here, we surveyed transcriptomes of the wild-type strain M. aeruginosa PCC 7806 and the microcystin-deficient ⌬mcyB mutant under low light conditions with and without the addition of external MC of the LR variant (MC-LR). Transcriptomic data acquired by microarray and quantitative PCR revealed substantial differences in the relative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 46 publications
2
50
0
3
Order By: Relevance
“…These findings are in agreement with results from Makower et al. (), where the authors found a nonsignificant upregulation of mcyA gene when adding 50 μg L −1 microcystin‐LR.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with results from Makower et al. (), where the authors found a nonsignificant upregulation of mcyA gene when adding 50 μg L −1 microcystin‐LR.…”
Section: Discussionsupporting
confidence: 93%
“…Glutathione conjugation most commonly occurs via a nucleophilic attack by the glutathione cysteinyl thiol on an electrophilic carbon such as a lactone or epoxide (Wang and Ballatori, 1998). The γ-glutamyl residue can then be cleaved by a γ-glutamyl transpeptidase localized outside the plasma membrane, leaving the conjugated Cys-Gly, as occurs in the case of the glutathione-modified microcystin (Schmidt et al, 2014), a cyanobacteria toxin and intra- and extra-cellular signaling molecule (Makower et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…As more evidence supporting the role of MC related to oxidative stress, several studies showed an increased sensitivity of MC-deficient mutants under high light and oxidative stress conditions (Zilliges et al, 2011;Meissner et al, 2015;Makower et al, 2015). In addition, Briand et al (2008) observed a decrease in MC cell quota in the late exponential growth phase.…”
Section: Discussionmentioning
confidence: 99%